Dynamic effects of biochar concentration and particle size on hydraulic properties of sand. (8th March 2018) - Trifunovic, Branimir; Gonzales, Howell B.; Ravi, Sujith; Sharratt, Brenton S.; Mohanty, Sanjay K.
Abstract: Large‐scale application of biochar has been promoted as a strategy for improving soil quality in agricultural and contaminated lands, as biochar has the potential to alter soil physical and biogeochemical properties. Biochar at different concentrations has been shown to have inconsistent effects on soil hydrological properties, yet the cause of the inconsistency is not well understood. To investigate the relative roles of biochar size and concentration, we mixed pure sand with a commercially available biochar varying its concentrations and particle sizes and measured saturated ( K sat ) and unsaturated hydraulic conductivity and water‐retention characteristics. An increase in the concentration of fine biochar (<2 mm) consistently decreased K sat and increased saturated moisture content. In contrast, an increase in the concentration of unsieved (mixture of coarse and fine) biochar up to 5% (by volume) increased K sat, whereas any further increases in unsieved biochar concentration decreased K sat . Increase in biochar concentration, irrespective of particle size, consistently decreased the unsaturated hydraulic conductivity. Measuring the changes in the characteristics of water‐retention curves of biochar–sand mixtures with biochar particle size, we showed that added biochar can either decrease (clog) or increase pore spaces in the mixture on the basis of the quantity of fine biochar fraction, which in turn could decrease or increase the hydraulic conductivity of the mixture. Thus, biochar concentration and particle size must be taken into consideration to maximize the intended hydrological benefits of biochar amendment.